Assessing self-medication for obstructive airway disease during COVID-19 using Google Trends. Issue 5 (19th November 2020) - Sahanic, Sabina; Boehm, Anna; Pizzini, Alex; Sonnweber, Thomas; Aichner, Magdalena; Weiss, Guenter; Loeffler-Ragg, Judith; Tancevski, Ivan
COPD is a leading cause of morbidity and mortality worldwide, affecting approximately 294 million people worldwide, and accounting for over 3 million deaths annually. Similarly, asthma affects approximately 268 million people worldwide, leading to an enormous health burden [1]. With the outbreak of the coronavirus disease 2019 (COVID-19) pandemic, the Global Initiative for Chronic Obstructive Lung Disease (GOLD) set a main emphasis on recommendations focused on the regular use of bronchodilator maintenance therapy, and the Global Initiative for Asthma (GINA) guidelines 2020 explicitly state that inhaler therapy, especially the maintenance therapy with inhaled corticosteroids (ICS), should not be interrupted during the pandemic [2, 3]. Google Trends reveals public information-seeking for self-medication in patients with obstructive respiratory disease during the COVID-19 outbreak, illustrating the urgent need to implement digital health support in patients with respiratory disease https://bit.ly/2GRccSU